Visual Expression of Insight Through Nature - Janette Kiara Zerlinda Santosa; Ariesa Pandanwangi; Wawan Suryana (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
Nature inspires many artists, and is explored through visual expression using various media and techniques. Various streams that visualize this include realism or naturalism. These visual expressions can represent and record nature. Visual expressions that are conveyed in an abstract form that can provide a natural atmosphere by bringing calm, comfort, have not been explored by many artists both from within and outside the country. This creation aims to find out how to convey a calm situation through art works to art appreciators. The benefit of this creation for the development of society is that it can create a "reflective effect" for the public, both visually and spiritually/psychically. This art creation method uses qualitative descriptive and exploratory methods. The process of collecting data through library research, and searching on the internet. The results of the art creation process are 4 works that carry the theme of inner peace using oil paint on canvas measuring 60 x 60 cm. The composition of the 4 works is dominated by center and asymmetrical compositions. Coloring is dominated by using cheerful and contrasting colors, namely blue, yellow, green, white and a mixture of these colors. The conclusion of this creation is that the appreciator can capture natural objects that are visualized in each work.